2016
DOI: 10.1371/journal.pone.0158001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Vitreous Humor in Retinal Vein Occlusion

Abstract: PurposeTo analyze the protein profile of human vitreous of untreated patients with retinal vein occlusion (RVO).MethodsSixty-eight vitreous humor (VH) samples (44 from patients with treatment naïve RVO, 24 controls with idiopathic floaters) were analyzed in this clinical-experimental study using capillary electrophoresis coupled to mass spectrometer and tandem mass spectrometry. To define potential candidate protein markers of RVO, proteomic analysis was performed on RVO patients (n = 30) and compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…By combining iTRAQ labeling with 2D-nano-LC-MS/MS, 1030 proteins were identified with 6078 peptides, of which 2613 correspond to unique peptides ( Supplementary Table S1 ). To recognize which proteins were newly found in the present study, the identified proteins were compared to previous vitreous proteomics reports [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], as seen in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining iTRAQ labeling with 2D-nano-LC-MS/MS, 1030 proteins were identified with 6078 peptides, of which 2613 correspond to unique peptides ( Supplementary Table S1 ). To recognize which proteins were newly found in the present study, the identified proteins were compared to previous vitreous proteomics reports [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], as seen in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, 1030 proteins were identified with 6078 peptides, of which 2613 correspond to unique peptides. These proteins were compared to previous vitreous proteomics reports ( Supplementary Table S2 ), including twelve studies in which vitreous were collected by pars plana vitrectomy [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 ] and one study in which vitreous core was aspirated from post-mortem healthy eyes [ 34 ]. Table 3 displays the total number of proteins identified in the vitreous using distinct experimental set-ups, including the number of proteins found exclusively in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies using proteomic, nucleic acid, and lipidomic approaches identified interesting potential vitreal biomarkers in retinal vein occlusion (Reich et al, 2016), neovascular AMD (Menard et al, 2016; Nobl et al, 2016), diabetic retinopathy (Jin et al, 2016), and primary open-angle glaucoma (Agnifili et al, 2015). However, none of these studies explored or discussed the role of exosomes or other EVs in the transport to and presence of biomarkers in the VH.…”
Section: Exosome Biomarkers For Eye Diseasesmentioning
confidence: 99%
“…An interesting study on protein analysis in the vitreous humor of the eye was reported by Reich et al. . These investigators examined patients with retinal vein occlusion and compared them to a set of controls.…”
Section: Applications In Different Clinical Fieldsmentioning
confidence: 99%